Ethics and deontology in information systems - Evolution of professional codes - Ribeiro, Diana (2023)
Information Systems professionals deal daily with ethical dilemmas, which are most notorious when making decisions. Due to the importance of ethical behavior and to prevent unethical situations without full awareness of them, the development of codes of ethics and conduct for companies and communities of professionals has been fundamental. Since the creation of the first code of ethics in computing in 1972, many codes of ethics and conduct have emerged from the initiative of various societies, organizations, and associations all over the world. This article identifies and describes the structural evolution of the main codes in the Information Systems area, from the original to the most recent versions. From analyzing the codes, the following results were obtained: (1) codes of ethics and codes of conduct are the most common code types; (2) the codes are directed mainly at all members of the entities (without differentiation); (3) the evolution of codes is related to the changing of descriptions of conducts, the changing of the structure of documents, and in many cases there is an increase of the number of conducts of ethical behavior in the newer versions of the codes.